2010
DOI: 10.33073/pjm-2010-044
|View full text |Cite
|
Sign up to set email alerts
|

Biodeterioration of Optical Glass Induced by Lubricants Used in Optical Instruments Technology

Abstract: The process of biodeterioration of optical glass was studied after being induced by an auxiliary material (lubricant 4CKP) used in the production of optical instruments. It was determined that the lubricant can initiate growth of conidia of Aspergillus niger fungus. Acid spawn metabolites cause deterioration of the glass surface. Measurements of laser light beam transmittance through the glass plate and the AAS chemical analysis method of the post-culture fluid allowed to determine that glass with a high SiO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
5
0
1
Order By: Relevance
“…Staining, etching, biopitting, and crystal formation were also observed, even after the cleaning procedure (Figure 2 and Appendix A, Figure A2a, marked as 'B', 'E', and 'F', respectively). The darkening of glass surfaces from deterioration processes is often associated with fungal growth [19]. Penicillium chrysogenum spores produced biological colonisation and mycelium growth (with hyphae reaching the edges) in all glass samples (Appendix A, Figure A2b).…”
Section: Surface Morphology: Optical and Scanning Electron Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Staining, etching, biopitting, and crystal formation were also observed, even after the cleaning procedure (Figure 2 and Appendix A, Figure A2a, marked as 'B', 'E', and 'F', respectively). The darkening of glass surfaces from deterioration processes is often associated with fungal growth [19]. Penicillium chrysogenum spores produced biological colonisation and mycelium growth (with hyphae reaching the edges) in all glass samples (Appendix A, Figure A2b).…”
Section: Surface Morphology: Optical and Scanning Electron Microscopymentioning
confidence: 99%
“…Similar deterioration patterns were reported by other authors-e.g., Kerner-Gang [20] who also reported pits on the glass surface caused by Aspergillus versicolor conidia (spores). Bartosik et al [19] reported the development of conidia of the fungus Aspergillus, together with glass biodeterioration features.…”
Section: Surface Morphology: Optical and Scanning Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Các kết quả đạt được cho thấy, quá trình đồng nhiễm nấm xảy ra trên bề mặt thấu kính của ống nhòm. Mật độ trung bình của nấm sợi trong nghiên cứu này khá tương đồng với các công bố liên quan đến nấm gây hại kính Tu viện Cartuja de Miraflores, Burgos, Tây Ban Nha [28,29], kính nhà thờ tại Belém do Pará, Brazil [14] và kính cửa sổ tại Mỹ [13].…”
Section: đặC đIểm Mẫu Vật Kính ốNg Nhòm Gây Hại Bởi Nấm Sợiunclassified
“…Laboratory tests on unglazed ceramic roof tiles have shown that fungi are able to form bioprecipitates and penetrate into pores affecting the material integrity [16,17]. In addition, several studies focused on stained glass windows from cultural heritage assets [18][19][20] and laboratory-based colonization experiments [14,15,21,22] have provided important insights into glass biodeterioration by fungi, showing that they able to cause glass biocorrosion. Yet, studies on the biodeterioration of glazed tiles have mainly focused on the identification of colonizing microorganisms [4][5][6]8,10] and no laboratory experiments have been performed on fungal biodeterioration of historical glazed ceramic tiles.…”
Section: Introductionmentioning
confidence: 99%